Seven New Series and Four New Species in Sections Subinflati and Trachyspermi of Talaromyces (Trichocomaceae, Eurotiales) - Lu-Yao Peng; Xin-Cun Wang; Yusufjon Gafforov; Wen-Ying Zhuang (Journal of Fungi)
Species of Talaromyces C.R. Benj. are valuable biological resources for human beings as competent producers of enzymes, antibiotics, antifungal agents and biopigments, but a comprehensive taxonomic system at the series level has not been fully provided for this genus. In this study, three new series, Palmarum, Resedani and Subinflati, are proposed in section Subinflati. Section Trachyspermi is also restructured to include five series, in which Diversi, Erythromelles, Miniolutei and Resinarum are newly erected, and Trachyspermi is emended. Additionally, four new species are discovered: T. elephas, T. sinensis and T. xishuangbannaensis isolated from rotten fruit husk in Yunnan Province, China, belonging to the series Erythromelles, Subinflati and Miniolutei, respectively, and T. tianshanicus from soil in Uzbekistan, located in ser. Diversi. Morphological distinctions, including colony characteristics, conidiophore structures, and conidial morphologies, along with phylogenetic analyses based on multi-locus datasets (ITS, BenA, CaM and RPB2), confirm their novelty to science. Detailed descriptions and illustrations of the new species are given. The proposed classification of Talaromyces at the series level provides a refined infrageneric framework and facilitates taxonomic stability and future biodiversity studies.